Health education method to improve anemia prevention knowledge in adolescents - Adelia Firandi; Ika Norcahyanti; Mikhania Christiningtyas Eryani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Based on data from Riskesdas, the highest prevalence of anemia occurs in pregnant women (48.9 percent and adolescent girls aged 15-24 years (32 percent. Adolescent girls are a high-risk group for anemia due to blood loss during menstruation and the possibility of micronutrient deficiencies. Other identified causes include improper eating patterns and low adherence to consuming iron supplementation tablets (IST). To increase public knowledge about anemia, education is needed, one of which can be conducted through outreach in schools. This counseling aims to determine the students' level of understanding regarding anemia, which can subsequently enhance their knowledge and compliance with iron tablet consumption. The counseling was conducted at SMP Negeri 14 Jember on February 25, 2025, and attended by 32 student council members. The material was delivered through a PowerPoint presentation, leaflets, and games. Evaluation was conducted using a comparison of pre-test and post-test results to measure changes in students' knowledge about anemia. The results show an increase in knowledge among 71.88 percent of students, and from the statistical test results using the paired T-test, a significant result was obtained p<0.05. Based on this, educational activities aimed at preventing anemia using a counseling approach can enhance adolescents' understanding of anemia.